SEXUAL ABUSE: DEVELOPMENTAL CONSIDERATIONS FOR FORMATION - Noronha, Konrad J. (Asian Horizons, 2020)
Attention needs to be paid to the overall growth of seminarians and clergy and religious. The focus has to be on the four dimensions of human formation, and any deficiency needs to be addressed early in formation of the seminarian and through ongoing formation of the clergy and religious. This might help in averting untoward mishaps with regard to misconduct or inappropriate behaviour. Integrity or uprightness is what is called for in Catholic clergy and religious. Because of lack of this virtue some fell prey to misconduct that includes sexual abuse. This article looks at sexual abuse in general and sexual abuse in particular through various theories that include the biological, physiological, neuromoral, psychological, and moral theories of development. Some developmental programs and interventions are also discussed. The Holy Father has called all clergy and religious to open their hearts to the immensity and the importance of the task of safeguarding of minors and vulnerable adults.